Improving Reading Comprehension Ability of Class X Students at SMK Negeri 7 Semarang Material Unggah-ungguh Basa in Narrative Texts Through Differentiated Learning - Rinnjani, Wahyu Tia; Yuliawati, Aida; Fateah, Nur (Universitas PGRI Semarang, 2024)
The aim of this research is to describe the ability of class Through Javanese learning activities, students are expected to be able to master several skills such as listening, speaking, reading and writing. However, in achieving learning goals, especially in terms of reading comprehension, students often experience difficulties. There are several factors that can influence students in reading comprehension activities, namely the lack of vocabulary that students have so that students tend not to understand and understand the reading material they are reading. Apart from that, another factor is the use of language uploads which are not applied enough in everyday language speech, making students less familiar with them and experiencing many errors in their application. This research uses the classroom action research method or (CAR). The data obtained in this research was collected through observation and student questionnaires. The results of this research show that class